2023
DOI: 10.1091/mbc.e23-01-0006
|View full text |Cite
|
Sign up to set email alerts
|

A conserved STRIPAK complex is required for autophagy in muscle tissue

Abstract: Autophagy is important for cellular homeostasis and to prevent the abnormal accumulation of proteins. While many proteins that comprise the canonical autophagy pathway have been characterized, the identification of new regulators may help understand tissue and/or stress-specific responses. Using an in silico approach, we identified Striatin interacting protein (Strip), MOB kinase activator 4 (Mob4), and Fibroblast growth factor receptor 1 oncogene partner 2 (Fgop2) as conserved mediators of muscle tissue maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The selection of individual STRIPAK components in the LFQ Results Table allows for a comparison of protein abundance in either bait or control pull-down datasets ( Figure 3 F). Both physical and genetic interactions among STRIPAK complex members are well validated in multiple systems and across organisms, 1 , 16 , 17 , 18 , 19 , 20 , 21 thus demonstrating the robustness of our approach.…”
Section: Expected Outcomesmentioning
confidence: 74%
See 1 more Smart Citation
“…The selection of individual STRIPAK components in the LFQ Results Table allows for a comparison of protein abundance in either bait or control pull-down datasets ( Figure 3 F). Both physical and genetic interactions among STRIPAK complex members are well validated in multiple systems and across organisms, 1 , 16 , 17 , 18 , 19 , 20 , 21 thus demonstrating the robustness of our approach.…”
Section: Expected Outcomesmentioning
confidence: 74%
“…We recently used this strategy to identify muscle-enriched proteins that function with Strip in the STRIPAK complex. 1 In addition to the FLAG-Strip pull-down experiments, we also performed AP-MS pull-downs using transgenic flies that express a V5 tag on the C-terminus of Strip (Strip-V5). Proteins common in both pull-downs using a Venn diagram were considered for further analysis.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Autophagy is another programmed cell death pathway that is involved in the sequestration of cytoplasmic proteins and organelles for recycling and tissue remodeling [59,246,274,275,[354][355][356][357][358]. Most descriptions of autophagy involve macroautophagy, rather than microautophagy or chaperone-mediated autophagy [59,359], which can form autophagosomes for combining into lysosomes.…”
Section: Cellular Mechanisms Of Oxidative Stress Energy Metabolism An...mentioning
confidence: 99%
“…The processing of circulating oxidized fatty acids during DM may require autophagy activation [18,165], and mitochondrial homeostasis can be dependent upon the activation of autophagy pathways [46]. Maintenance of autophagic flux during DM also may be one factor in preserving cognition [77,371], maintaining muscle integrity [354], fostering the function of pancreatic β-cells [372], decreasing insulin resistance in models of autophagy Atg7 gene deletion and obesity [373], blocking nephropathy during DM with maintenance of autophagy Atg7, Atg5, and microtubule-associated protein 1A/1B-light chain 3 (LC3) proteins [374], and controlling the development of pancreatic β-cells [375]. Yet, a balance in autophagy activation is necessary since autophagy also can lead to detrimental effects.…”
Section: Cellular Mechanisms Of Oxidative Stress Energy Metabolism An...mentioning
confidence: 99%
“…A recent study has revealed interaction between STRN1 and ULK1 (Unc-51 Like Autophagy Activating Kinase 1) in a positive-feedback manner via PP2A, promoting cell autophagy [ 75 ]. The implication of STRIPAK in autophagy within muscle tissues has additionally been demonstrate in cancer research [ 76 , 77 ]. Although MAP4K2, a GCKI family member, is not considered a STRIPAK member, the depletion of STRN4 induces hyperphosphorylation and activation of MAP4K2, suggesting a crucial regulatory role of STRIPAK upstream to MAP4K2.…”
Section: Cellular Function Of Strns and The Stripak Complexmentioning
confidence: 99%